Control of a high voltage gain dc-dc boost converter using the Arduino microcontroller - Ong, Li Ting (Nanyang Technological University, 2020)
In this report, the regulation of a super-lift re-lift (SLRL) Luo converter using an Arduino Due is described. The super-Lift Re-Lift (SLRL) Luo converter is an improved version converter as compared to the conventional DC-DC boost converter. It produces a higher output voltage as compared to the conventional converter. Depending on the required output voltage, different level of lift cells can be added. The design and implementation of the converter and three different controllers are presented in this report. Some experimental results are also given to illustrate the performance of the controllers implemented using the Arduino Due.